2017
DOI: 10.1002/hep4.1025
|View full text |Cite
|
Sign up to set email alerts
|

Interferon‐alpha‐induced hepatitis C virus clearance restores p53 tumor suppressor more than direct‐acting antivirals

Abstract: The mechanism why hepatitis C virus (HCV) clearance by direct‐acting antivirals (DAAs) does not eliminate the risk of hepatocellular carcinoma (HCC) among patients with advanced cirrhosis is unclear. Many viral and bacterial infections degrade p53 in favor of cell survival to adapt an endoplasmic reticulum (ER)‐stress response. In this study, we examined whether HCV clearance by interferon‐alpha or DAAs normalizes the ER stress and restores the expression of p53 tumor suppressor in cell culture. We found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 24 publications
1
35
0
Order By: Relevance
“…We showed that CMA activation by stress degrades p14ARF, another alternative open reading frame protein (ARF), a tumor suppressor that activates p53. 136 The subsequent publication showed that excessive ER stress induces MDM2-mediated Rb degradation. 137 All these results are consistent with human studies that show more than 70% of HCC cases having alterations in the p53-Rb pathway that leads to mitosis, cell cycle progression, and genomic instability.…”
Section: Telomerase Reverse Transcriptase (Tert)mentioning
confidence: 99%
See 2 more Smart Citations
“…We showed that CMA activation by stress degrades p14ARF, another alternative open reading frame protein (ARF), a tumor suppressor that activates p53. 136 The subsequent publication showed that excessive ER stress induces MDM2-mediated Rb degradation. 137 All these results are consistent with human studies that show more than 70% of HCC cases having alterations in the p53-Rb pathway that leads to mitosis, cell cycle progression, and genomic instability.…”
Section: Telomerase Reverse Transcriptase (Tert)mentioning
confidence: 99%
“…194 We showed that HCV-induced cellular ER stress could activate MDM2 that degrades Rb tumor suppressor independent of p53. 136 A recent report shows that MDM2 can associate with the PRC2 and enhances stemness through chromatin modification independent of p53. 195 This evidence suggests there are many oncogenic pathways that HCV replication probably induces epigenetic cell programing that induces CSCs leading to HCC.…”
Section: Cancer Stem Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…Among Nrf2 target genes, Hsc70 and LAMP2 are upregulated in their transcription, consequently activating CMA (Aydin et al, 2018). The activation of CMA leads to lysosomal degradation of both pro-autophagic protein BECLIN 1, thus impairing autophagy, and the tumor suppressor p53 (Aydin et al, 2017(Aydin et al, , 2018. Accordingly, it has been shown that HCV replication is able to suppress p53 functions and that p53 protein levels are low in HCV-infected explanted livers (Aydin et al, 2017).…”
Section: Hepatitis C Virusmentioning
confidence: 99%
“…The activation of CMA leads to lysosomal degradation of both pro-autophagic protein BECLIN 1, thus impairing autophagy, and the tumor suppressor p53 (Aydin et al, 2017(Aydin et al, , 2018. Accordingly, it has been shown that HCV replication is able to suppress p53 functions and that p53 protein levels are low in HCV-infected explanted livers (Aydin et al, 2017). Previous studies have reported that CMA compensate impaired autophagy in the cirrhotic liver to promote hepatocellular carcinoma (Chava et al, 2017).…”
Section: Hepatitis C Virusmentioning
confidence: 99%